Economic performance and turnout at national and local elections - Martins, Rodrigo (2013)
This paper analyzes the impact of economic performance on voter turnout. We estimate an economic turnout model in which local economic variables are included in quadratic form, so that non-linear effects can be taken into account. We use panel datasets covering municipalities, from 1979 to 2005, and cross-sections of parishes (freguesias) to analyze the determinants of turnout at Portuguese municipal and legislative elections. The empirical results indicate that the performance of the national economy is important only in legislative elections and that the regional and local unemployment rates tend to have non-linear relationships to turnout. The results obtained for Flemish municipalities also provide evidence in favor of a non-linear effect of unemployment on turnout.